PENGARUH PERCEIVED SERVICE QUALITY TERHADAP UNIBRAND PERFORMANCE MELALUI SATISFACTION PADA UNIVERSITAS SWASTA - Mega Arti Utami (Jurnal Manajemen dan Pemasaran Jasa, 2015)
This study refers to an earlier study that has been done by Sultan & Wong (2014). Thepurpose of this study was to determine the influence of Perceived Service Quality on the UniBrand Performance through Satisfaction in Private Universities. The design of this research is hypothesis testing using primary data obtained by distributing questionnaires directly to the 200 respondents who were active students of Private Universities in Jakarta. The analytical method used is Structure Equation Model (SEM). The result of this research conclude that there is a significant and positiverelation between Perceived Service Quality and Satisfaction. There is a significant and positive relation between Satisfaction and UniBrand Performance. There is a significant and positive relation between Perceived Service Quality and UniBrand Performance.